Prensa española, ante la condena de la ONU a Israel por la invasión a Gaza - Pablos Coello, José Manuel de (Estudios sobre el Mensaje Periodístico, 2009)
A group of fourteen members of the United States Congress assure that “the main Spanish medias” are anti- Semite because of their position before the Israeli invasions to Gaza in 2008 – 2009. To confirm the position of the local and national Spanish newspapers before the situation we have study which have been their political leading article though a peculiar note; the sentence done in New York by the Secretary General of the United Nations by the destruction of the UN´s installations in the border of Gaza during the invasions. For this, we have to analyze thoroughly the news and to assure the treatment given for each of the five national newspapers already analyzed ABC, El Mundo, El País, La Razón y Público.
Keywords: Spanish press; Gaza; Israel; United Nations; Sentences of the ONU to Israel; Anti- Semite